Hubungan Kecanduan Gawai dengan Kejadian Insomnia pada Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Surabaya - Gina Noor Djalilah; Lucky Dyah Oktaviyanti; Era Catur Prasetya; Nina Devi Indrawati; Adi Satria Nugraha (Universitas Muhammadiyah Surabaya, 2024)
Insomnia is a condition characterized by difficulty falling asleep, staying asleep, or waking up early despite having the opportunity to sleep. Insomnia can reduce the quality and quantity of sleep, leading to various negative effects on an individual's health and well-being. One of the potential causes of insomnia is excessive smartphone use, which can lead to addiction. Smartphone addiction can affect people of all ages, from children to adults. It has been associated with several adverse effects, including insomnia, recurrent and prolonged headaches, and fatigue. This study aimed to investigate the relationship between smartphone addiction and insomnia among medical students at the University of Muhammadiyah Surabaya. This cross-sectional observational study involved 87 medical students from the 2019, 2020, 2021, and 2022 cohorts. The sample was selected using a proportionate stratified random sampling technique. Data were collected using the Smartphone Addiction Scale (SAS) and the Insomnia Rating Scale (KSPBJ-IRS) through a Google form. The data were analyzed statistically using the Chi-square test in SPSS version 25. The Chi-square test showed a p-value of 0.005 (<0.05), indicating a statistically significant relationship between smartphone addiction and insomnia among medical students at Muhammadiyah University of Surabaya. In conclusion, the study found a significant relationship between smartphone addiction and insomnia among medical students at Muhammadiyah University of Surabaya. This suggests that excessive smartphone use may contribute to sleep disturbances in this population.